Inhibitory Effects of Apigenin on Tumor Carcinogenesis by Altering the Gut Microbiota - Shichang Bian; Hongjuan Wan; Xinyan Liao; Weisheng Wang (Mediators of Inflammation)
The flavonoid apigenin is common to many plants. Although the responsible mechanisms have yet to be elucidated, apigenin demonstrates tumor suppression in vitro and in vivo. This study uses an azoxymethane (AOM)/dextran sodium sulfate- (DSS-) induced colon cancer mouse model to investigate apigenin’s potential mechanism of action exerted through its effects upon gut microbiota. The size and quantity of tumors were reduced significantly in the apigenin treatment group. Using 16S rRNA high-throughput sequencing of fecal samples, the composition of gut microbiota was significantly affected by apigenin. Further experiments in which gut microbiota were reduced and feces were transplanted provided further evidence of apigenin-modulated gut microbiota exerting antitumor effects. Apigenin was unable to reduce the number or size of tumors when gut microbiota were depleted. Moreover, tumor inhibition effects were initiated following the transplant of feces from mice treated with apigenin. Our findings suggest that the effect of apigenin on the composition of gut microbiota can suppress tumors.